PENGARUH TINGKAT SUKU BUNGA, TINGKAT INFLASI, DAN RASIO KEUANGAN TERHADAP BETA SAHAM - - Fidiana (Universitas Trunojoyo Madura, 2010)
This study investigated interest, inflation, and financial ratio consist of leverage, earnings variability, accounting beta, earnings per share, price earnings ratio, price book value, and dividend yield as independent variables that influence systematic risk. Dependent variables is systematic risk that proxied by beta. Population this study are public companies listed in Indonesian Stock Exchange.Samples used in this research are selected using purposive sampling from public companies of Jakarta Islamic Indeks (JII) from 2001-2005. The research tested hypotheses by using multiple regression analysis models. Based on model used, the results with F-test or Anova show that interest, inflation, and financial ratio significant influence on syariah stock beta. The result show thad interest and inflation did not influent to systematic risk. The results also show that from the nine factors of financial assumed influent to syariah stock beta, there are three factors which partially show significant influence consist of: leverage, earnings variability, and price book value.